PENGARUH PROFITABILITAS, LIKUIDITAS, SOLVABILITAS, DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ega Arminta, 15.05.52.0275; Suwarti, Titiek (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the effect of profitability, liquidity, solvency, and firm size on stock returns in property and real estate companies listed on the Indonesia Stock Exchange. The population in this study are all property and real estate companies that are listed on the Indonesia Stock Exchange. The sample selection uses a purposive sampling method. The analytical tool used in this study is multiple linear regression analysis with 108 observation data for the period 2015-2017. The test results show that Profitability have no significant and negative effect, Liquidity have a significant and positive effect, Solvability have a positive and insignificant effect, and Firm Size have a significant and negative effect on stock returns.